Patient registers and account registries of compulsory medical insurance: integration and replaceability - I. A. Zheleznyakova; G. I. Pirova; E. A. Proxorovich (IRBIS LLC, 2019)
Patient registers are an effective tool for monitoring the disease incidence in the population and the effectiveness of medical care provided to patients. The registers also represent a source of information for making organizational decisions on the healthcare system. The aim of this study is to review the regulatory and legal acts governing the patient registers, and compare them with the registers of compulsory medical insurance (CMI) accounts to assess the possibility of integrating the data into a unified registry based on the CMI accounts.